PERTANGGUNGJAWABAN PIDANA PARTAI POLITIK YANG MELAKUKAN TINDAK PIDANA - Wahyu Wahyu (Arena Hukum, 2014)
AbstractPolitical party is alegal entityorganization. Itcan take legal actions through the organs of the political party.This writing intent onÂ knowingÂ whether political party belongs to law institution/body or not which can be asked for the criminal liability and also finding the conception of the criminal liability of political party that commit a crime. This writing has made according to normative research which used statute approach, historical approach, and conceptual approach. The result from this research shows that political party is a law institution/body which can be asked for the criminal liability because of the characteristic from political party which appropriate for law institution/body characteristics. It is in line with the criminal liability theory for corporation which mentions that an action or a delict and an individual default (political party management) who acts for and/or as a representative of that political party is automatically be a political party default. The criminal liability concept of political party shows that political party as a criminal law subject are the political party management as a subject of crime and the management who is responsible, political party as a subject of crime and the management who is responsible, political party as a subject of crime and the political party who is responsible.Key words: the criminal liability, political party, commit a crime Â Abstrak Partai politik adalah organisasi yang berbadan hukum. Partai politik dapat melakukan perbuatan hukum melalui organ-organ dari partai politik tersebut. Tulisan ini bertujuan untuk mengetahui apakah partai politik termasuk badan hukum yang dapat dikenai pertanggungjawaban pidana serta untuk menemukan konsep pertanggungjawaban pidana terhadap partai politik yang melakukan tindak pidana. Tulisan ini dibuat berdasarkan penelitian normatif yang menggunakan pendekatan perundang-undangan, pendekatan sejarah, dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa partai politik adalah badan hukum yang dapat dikenai pertanggungjawaban pidana karena dari karakteristik partai politik yang sesuai dengan karakteristik badan hukum, hal ini sejalan dengan teori pertanggungjawaban pidana korporasi yang menyatakan suatu perbuatan atau tindak pidana dan kesalahan seseorang individual (pengurus partai) yang bertindak untuk dan/atau atas nama badan hukum (dalam hal ini partaipolitik)secara otomatis menjadi perbuatan atau kesalahan dari badan hukum partai politik. Konsep pertanggungjawaban pidana partai politik menunjukkan bahwa partai politik sebagai subjek hukum pidana, yaitu pengurus partai politik sebagai pelaku dan pengurus yang bertanggung jawab, partai politik sebagai pelaku dan pengurus partai politik yang bertanggung jawab, partai politik sebagai pelaku dan partai politik yang bertanggung jawab.Kata kunci: pertanggungjawaban pidana, partai politik, melakukan tindak pidana